2013
DOI: 10.1111/j.1440-1843.2012.02278.x
|View full text |Cite
|
Sign up to set email alerts
|

Septic pulmonary embolism due to periodontal disease

Abstract: Most patients with SPE-PD were not seriously ill. Contrast-enhanced chest CT appeared to be useful to diagnose SPE-PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
(20 reference statements)
1
13
1
Order By: Relevance
“…In the 2000s, Cook et al reported that Lemierre syndrome and central venous catheter infection were the common causes of SPE [3]. Moreover, two studies from Taiwan and one from Japan reported on SPE cases caused by liver abscesses [16, 17] and periodontal disease [7], respectively. Recently, several studies demonstrated that bone, skin, and soft tissue infections are the most common source of infection [4, 6, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2000s, Cook et al reported that Lemierre syndrome and central venous catheter infection were the common causes of SPE [3]. Moreover, two studies from Taiwan and one from Japan reported on SPE cases caused by liver abscesses [16, 17] and periodontal disease [7], respectively. Recently, several studies demonstrated that bone, skin, and soft tissue infections are the most common source of infection [4, 6, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Septic pulmonary embolism (SPE), unlike the much more common thrombotic pulmonary embolism, is a rare disorder in which a bacterial embolus containing microorganisms originating from the primary extrapulmonary infectious foci [1] (such as liver abscesses [2], peritonsillar abscesses [3], infection of skin and bone [4], infective endocarditis [5, 6], periodontal disease [7], intravascular devices and catheters [3]) obstructs the small pulmonary vasculature, causing sepsis and a focal abscess in the lung. SPE is associated with a high mortality rate and remains a diagnostic challenge in clinical practice due to its insidious onset, nonspecific clinical manifestations (such as fever, cough, dyspnea, chest pain and hemoptysis), and life-threatening complications [8].…”
Section: Introductionmentioning
confidence: 99%
“…Articles published from January 1, 1980 to September 1, 2018 were included. A literature review disclosed thirty-seven previously reported cases of periodontal disease-associated SPE including the present case (Table 1) [2, 3, 5–18]. The case definition for periodontal disease-associated SPE included: (A) focal or multifocal lung filtrates compatible with septic embolism to the lung, (B) presence of periodontal disease, and (C) absence of other active extrapulmonary infection as a potential cause of SPE, which were confirmed for each case of previously reported periodontal disease-associated SPE.…”
Section: Discussionmentioning
confidence: 99%
“…The case definition for periodontal disease-associated SPE included: (A) focal or multifocal lung filtrates compatible with septic embolism to the lung, (B) presence of periodontal disease, and (C) absence of other active extrapulmonary infection as a potential cause of SPE, which were confirmed for each case of previously reported periodontal disease-associated SPE. The definition was a slightly modified version of those reported by Cook et al [4] and Hatani et al [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation